Case Report: FDG-PET/CT findings in co-infection of visceral leishmaniasis and chronic hepatitis B - Feng, Hui; Dai, Wenli (Frontiers in Cellular and Infection Microbiology, 2023)
Visceral leishmaniasis is an opportunistic infection in immunocompromised patients. Herein, we report a case of an adult male patient with a persistent fever of unknown origin, along with chronic hepatitis B. The patient underwent bone marrow aspiration twice, which revealed hemophagocytosis. Abdomen enhanced CT revealed splenomegaly with a persistent strengthening of multiple nodules, and hemangiomas were diagnosed. A subsequent 18-fluoro-deoxyglucose (18F-FDG) PET/CT scan, which was implemented to search for the reason for the fever, showed diffuse splenic disease uptake, and splenic lymphoma was considered as the diagnosis. His clinical symptoms improved after receiving hemophagocytic lymphohistiocytosis (HLH) chemotherapy. However, the patient was readmitted for fever again only 2 months later. Splenectomy surgery is performed to confirm the diagnosis and classification of lymphoma. Visceral leishmaniasis was eventually diagnosed in a spleen specimen and the third bone marrow biopsy. He received treatment with lipid amphotericin B and remained recurrence-free for 1 year. In this paper, we aim to provide detailed information that will help further our understanding of the clinical symptoms and radiographic findings of visceral leishmaniasis.